FUNDAMENTALISME AGAMA : Telaah Artikel “Religious Fundamentalism” dalam Buku Introducing Anthropology of Religion; Culture of the Ultimate Karya Jack David Eller - Nur Kholis (Sabda: Jurnal Kajian Kebudayaan, 2018)
The discussion in the article "Religious Fundamentalism" has a background in the development of the global cultural situation in the 20th and 21st centuries which shows an atmosphere of "tension" due to the encounter of religion with modern culture and secularity. Religion seemed to feel threatened by modernity so that it carried out self-defense and simultaneously resisted. As a result of being confined to tension that is actually "self-created", according to Eller, religious fundamentalism appears with a ferocious, vindictive and sometimes violent character. This kind of character is increasingly entrenched for those who have similar emotions, attitudes, and puritanical religious orientations. The main message Eller conveyed is that religious fundamentalism is not a single and stand-alone phenomenon, but is interrelated with other cultural factors with high complexity.